Are the patient-rated wrist evaluation (PRWE) and the disabilities of the arm, shoulder and hand (DASH) questionnaire used in distal radial fractures truly valid and reliable?. Issue 1 (January 2018) - Kleinlugtenbelt, Y. V.; Krol, R. G.; Bhandari, M.; Goslings, J. C.; Poolman, R. W.; Scholtes, V. A. B.
Abstract : Objectives: The patient-rated wrist evaluation (PRWE) and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire are patient-reported outcome measures (PROMs) used for clinical and research purposes. Methodological high-quality clinimetric studies that determine the measurement properties of these PROMs when used in patients with a distal radial fracture are lacking. This study aimed to validate the PRWE and DASH in Dutch patients with a displaced distal radial fracture (DRF). Methods: The intraclass correlation coefficient (ICC) was used for test-retest reliability, between PROMs completed twice with a two-week interval at six to eight months after DRF. Internal consistency was determined using Cronbach's α for the dimensions found in the factor analysis. The measurement error was expressed by the smallest detectable change (SDC). A semi-structured interview was conducted between eight and 12 weeks after DRF to assess the content validity. Results: A total of 119 patients (mean age 58 years (sd 15)), 74% female, completed PROMs at a mean time of six months (sd 1) post-fracture. One overall meaningful dimension was found for the PRWE and the DASH. Internal consistency was excellent for both PROMs (Cronbach's α 0.96 (PRWE) and 0.97 (DASH)). Test-retest reliability was good for the PRWE (ICC 0.87) and excellent for the DASH (ICC 0.91). The SDC was 20 for the PRWE and 14 for the DASH. No floor or ceiling effects were found. The content validity was good for both questionnaires. Conclusion: The PRWE and DASH are valid and reliable PROMs in assessing function and disability in Dutch patients with a displaced DRF. However, due to the high SDC, the PRWE and DASH are less useful for individual patients with a distal radial fracture in clinical practice. Cite this article : Y. V. Kleinlugtenbelt, R. G. Krol, M. Bhandari, J. C. Goslings, R. W. Poolman, V. A. B. Scholtes. Are the patient-rated wrist evaluation (PRWE) and the disabilities of the arm, shoulder and hand (DASH) questionnaire used in distal radial fractures truly valid and reliable? Bone Joint Res 2018;7:36–45. DOI: 10.1302/2046-3758.71.BJR-2017-0081.R1.